2023
DOI: 10.3390/min13081064
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Soil Pollution and Remediation Strategies in Coal Mining Regions

Abstract: Coal remains a very important source of energy for the global economy. Surface and underground coal mining are the two major methods of coal extraction, and both have benefits and drawbacks. Surface coal mining can have a variety of environmental impacts including ecosystem losses, landscape alteration, soil destruction, and changes to surface and groundwater quality and quantity. In addition, toxic compounds such as heavy metals, radioactive elements, polycyclic aromatic hydrocarbons (PAHs), and other organic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 170 publications
0
2
0
Order By: Relevance
“…Acid mine drainage (AMD) occurs when pyrite and other sulfate metals (such as tailing pits and dams open exposed cuts, and ore and waste-rock piles) oxidize due to exposure to air and microbial activity in mining areas. Numerous studies have demonstrated the critical role that water plays in the distribution and mobility of PTEs in the vicinity of mining sites (Han et al 2017;Liao et al 2016;Rouhani et al 2023b). High levels of PTEs and sulfate, as well as low pH values, are features associated with AMD.…”
Section: Potentially Toxic Elementsmentioning
confidence: 99%
“…Acid mine drainage (AMD) occurs when pyrite and other sulfate metals (such as tailing pits and dams open exposed cuts, and ore and waste-rock piles) oxidize due to exposure to air and microbial activity in mining areas. Numerous studies have demonstrated the critical role that water plays in the distribution and mobility of PTEs in the vicinity of mining sites (Han et al 2017;Liao et al 2016;Rouhani et al 2023b). High levels of PTEs and sulfate, as well as low pH values, are features associated with AMD.…”
Section: Potentially Toxic Elementsmentioning
confidence: 99%
“…The exploitation of mineral resources generates various types of waste, which often contains high levels of heavy metals. The improper treatment of accumulation and discharge can lead to serious pollution of the water and soils in the mining area [6][7][8][9]. At present, land area contaminated by mining in China exceeds 2 million hectares and is increasing at a rate of 33,000-47,000 hectares per year [10].…”
Section: Introductionmentioning
confidence: 99%
“…As a special type of wetland, new wetland in coal mining subsidence area is obviously different from natural wetland and other types of constructed wetland in terms of formation process and human disturbance degree. Studies on coal mining subsidence land at home and abroad are more focused on subsidence land reclamation technology, subsidence land ecological restoration technology, and subsidence land restoration and management technology (Li et al 2022 ; Rouhani et al 2023 ; Bi et al 2018 ). There are relatively few studies on the evolution law of nascent wetland ecosystems in coal mining subsidence areas, which focus on the change of soil fertility, biochemical properties of soil, and microbial communities in subsidence areas (Ma et al 2019 ; Sun et al 2023 ; Fang et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%